If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2f + 4s = 590 Solving 2f + 4s = 590 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4s' to each side of the equation. 2f + 4s + -4s = 590 + -4s Combine like terms: 4s + -4s = 0 2f + 0 = 590 + -4s 2f = 590 + -4s Divide each side by '2'. f = 295 + -2s Simplifying f = 295 + -2s
| -3(x+4)=2(x+5) | | 11y=9 | | 4x^3+16x^2-128x=0 | | 2x+4s=590 | | -3a+6+9=6a-2a | | 6x+22=-8x+2(1+2x) | | 5x+6=20-2x | | S^2=8+s(1-5) | | 13x-2(x+8)=8x+1 | | x+65+(x-5)=180 | | 4(z-2)+4z-4= | | -100w=1300 | | .18(18)+.03x=.06(12+x) | | 13x-2x(x+4)=8x+1 | | 2+3+4+5=18 | | 2x^3+14x^2+12x= | | -X-(13+4X)=-13+27X | | -6+2c=-10 | | 3(6)-3x=3 | | -3(4-x)=-27 | | 5x-3(x-5)=-7+4x+10 | | 2(x-4)+5=3(x+5)+2 | | 6+7q=11+6q | | 3x=14-10 | | 8y+9y+5y-6= | | x-(12-6)=3 | | 14+h/5=2 | | n+(-43)=102 | | 3x=4-10 | | 2m+1d=C | | 6x=3x+(x+1) | | 15x-3=25x+1 |